The impact of tomato pomace silage on feed utilization, health status, milk yield, and composition in dairy cows - Nirawan Gunun; Chatchai Kaewpila; Piyawit Kesorn; Thachawech Kimprasit; Metha Wanapat; Anusorn Cherdthong; Chanon Suntara; Waroon Khota; Pongsatorn Gunun (Animal Bioscience, 2026)
Objective: The aim of this study was to evaluate the effect of the inclusion of tomato pomace silage (TPS) on feed intake, nutrient digestibility, blood parameters, immune response, milk yield, and composition in dairy cows.Methods: Sixteen Thai Holstein dairy cows with a mean body weight of 621±20 kg and 240±15 d in milk were randomly assigned to a completely randomized design. The TPS was added at 0%, 10%, 20%, and 30% dry matter (DM) in a fermented total mixed ration. Each cow was given the diet ad libitum.Results: The nutrient intake was similar among treatments except for ether extract intake, which increased linearly (p